MICROPLASTIC ABUNDANCE AND MICROPLASTIC REMOVAL EFFICIENCY IN DRINKING WATER TREATMENT PLANT X (UNIT II) - Abiella Resmana, Amanda
The presence of microplastics in the environment is now growing and becoming a concern. The existence of microplastics is now found in terrestrial environment, and influenced by several factors, but mainly due to anthropogenic activities involving plastics consumption and the phenomenon of plastic fragmentation due to abiotic, biotic, and biological factors. Due to their small size (less than 5 mm), microplastics have now been found in aquatic animal cells, plant cells, and even in human organs. This threat results microplastics to be categorized as emerging contaminants of concerns. It is also estimated that 100.000 microplastics are consumed by humans per year. Knowing that microplastics may be present in the water, this study was conducted at water treatment plant (WTP) X Unit II. The WTP is in the northern Bandung area and using intake water from the Cisangkuy River and the Cikapundung River. This study is also aligned with the tendency of residents on the riverbanks around the study area to use boiled, piped water for consumption. This research was conducted to determine the abundance and the characteristic (color, shape, and size) of microplastics in WTP X Unit II, to determine the correlation between physical-chemical parameters of water, and to determine the microplastic removal efficiency in WTP X Unit II. Samples were taken at the intake points, as well as at the outlet of the coagulation-flocculation unit, sedimentation using a lamellae settler, and the filtration unit. The average abundance of microplastics from three sampling times at the Cisangkuy intake, Cikapundung intake, Mixed intake, flocculation outlet, sedimentation outlet, and filtration outlet were 32 particles/L, 36 particles/L, 38 particles/L, 46 particles/L, 32 particles/L, and 20 particles/L respectively, and a significant, positive correlation between TSS and turbidity on microplastic abundance is found. The most commonly found particle is in the fibrous form, the most abundant color found is black, and the most abundant size range is in the range of 300 – 1000 ?m. The microplastic removal efficiencies for coagulation-flocculation, sedimentation, and filtration were 9%, 30% and 56%, respectively, with filtration as the most optimal removal unit which showed significant result. In this study, only pigment compounds commonly found in the plastics industry were found on FT-IR analysis. Based on the comparative literature, the suspected polymers are polyester, polyethylene terephthalate (PET), Low Density Polyethylene (LDPE), Polypropylene (PP).